THE RELATIONSHIP OF ENGLISH WRITING MOTIVATION AND SELF-EFFICACY WITH ENGLISH WRITING ACHIEVEMENT OF GRADE 11 STUDENTS AT A DEMONSTRATION SCHOOL IN BANGKOK, THAILAND - Lesiuk, Anuthep; Lynch, Richard (Scholar: Human Sciences, 2022)
The aim of this study was to determine the relationship between the Grade 11 students’ English writing motivation and English writing self-efficacy with English writing achievement at a demonstration school in Bangkok, Thailand. The study used a quantitative correlational research design. For one of the instruments of this study, the English Writing Motivation and Self-Efficacy Questionnaire, the researcher adapted 30 items from Gardner’s (2010) Attitude/Motivation Test Battery (AMTB) and adopted 10 items from Wang, Kim, Bong and Ahn’s (2013) Questionnaire of English Self-Efficacy. The English Writing Motivation and Self-Efficacy Questionnaires was used to collect data on the Grade 11 students’ English writing motivation and English writing self-efficacy levels. The questionnaire was distributed to 64 Grade 11 students during February, 2020. The Grade 11 students’ in-school English Writing Examination was used to measure their English writing achievement. The in-school English Writing Examination was also distributed to the 64 Grade 11 students during March, 2020. Descriptive statistics (means and standard deviations) were used first to analyze the data. Multiple correlation coefficient analysis was then used to find the relationships among the Grade 11 students’ English writing motivation, English writing self-efficacy and English writing achievement. The findings showed that the Grade 11 students had a moderately high level of English writing motivation and a slightly high level of English writing self-efficacy. Furthermore, the findings indicated that there was a significant, moderately strong, positive relationship between English writing motivation and English writing achievement. English writing self-efficacy had a weak but positively significant relationship with English writing achievement. The findings also showed that English writing motivation had a moderately strong, significant, positive relationship with English writing self-efficacy. Finally, the findings revealed that there was a moderately strong, significant, positive relationship between English writing motivation and English writing self-efficacy with English writing achievement. Recommendations are provided for students’ support, teaching strategies and future research.